2019
DOI: 10.1590/s0004-2803.201900000-27
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Psychological Well-Being, Resilience and Coping With Social and Clinical Features in Crohn’s Disease Patients

Abstract: BACKGROUND: Crohn’s disease is chronic, requires prolonged treatment, affects the physical and psychosocial health of patients and may alter their routine, quality of life and well-being. Recent studies recommend monitoring the health of these patients considering physical, psychological and psychosocial aspects, because they are directly related to the disease activity. These studies highlight the relevance of patients’ emotional and behavioral conditions and suggest that the identification of the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Based on the review of past literature, Ryff and Singer (2003) revealed that resilient persons could protect their physical and psychological well-being, and bounce back from tense events. As Acciari et al (2019) stated, the levels of resilience and psychological well-being were interrelated. Ryff and Singer (2003) believed that maintaining mental and physical health, and the ability to recover faster from stressors characterize resilient individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the review of past literature, Ryff and Singer (2003) revealed that resilient persons could protect their physical and psychological well-being, and bounce back from tense events. As Acciari et al (2019) stated, the levels of resilience and psychological well-being were interrelated. Ryff and Singer (2003) believed that maintaining mental and physical health, and the ability to recover faster from stressors characterize resilient individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Ryff and Singer (2003) found that resilient people could safeguard their physical and PWB and recover from challenging situations based on a review of previous literature. According to Acciari et al (2019) , PWB and resilience levels were intertwined. According to Ryff and Singer (2003) , resilient people are those who can handle pressures while keeping their bodily and mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although IBD imposes a mental and physical toll on individuals [83], some individuals do report feeling stronger due to having IBD [84]. Most studies included in this review (Table 2) investigated psychological resilience and trait resilience that promoted the ability to bounce back from IBD-related adversity [85][86][87][88][89][90][91][92][93][94][95][96][97]. Some demographic characteristics found to be relevant to individuals with IBD included being optimistic, older [85], male, employed, not religious, and nulliparous [86].…”
Section: Resilience In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Some demographic characteristics found to be relevant to individuals with IBD included being optimistic, older [85], male, employed, not religious, and nulliparous [86]. Women with IBD more commonly reported resilience to be an essential determinant of health and both genders mentioned self-efficacy, social support, occupational balance, and job satisfaction as the main determinants of health [87]. Women with IBD and high resilience showed changes in brain-behavioural patterns, whereas the results were not conclusive for male participants [88].…”
Section: Resilience In Inflammatory Bowel Diseasementioning
confidence: 99%